1969
DOI: 10.21722/rbps.v17i1.12454
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da qualidade de vida em pacientes com hanseníase: uso do Medical Outcomes Study 36

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…En general, entre las profesiones más mencionadas por los entrevistados se encuentran: criadas, compañeros de albañilería y agricultores. Por lo tanto, asociado a varios otros componentes, es difícil cambiar la actividad profesional y la reubicación en el mercado laboral (15,18) .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…En general, entre las profesiones más mencionadas por los entrevistados se encuentran: criadas, compañeros de albañilería y agricultores. Por lo tanto, asociado a varios otros componentes, es difícil cambiar la actividad profesional y la reubicación en el mercado laboral (15,18) .…”
Section: Discussionunclassified
“…El DLQI se compone de 10 preguntas de opción múltiple, divididas en seis campos: trabajo, ocio, relaciones personales, tratamiento, síntomas y sentimientos, que evaluan al individuo desde el punto de vista dermatológico y se pueden utilizar para medir o comparar la calidad de la vida entre diferentes enfermedades de la piel. La puntuación del instrumento varía de 0-30, cuando 0 se atribuye al mejor resultado y 30 al peor, siendo: sin deterioro de la calidad de vida (0-1), con deterioro leve (2-5), moderado (6-10), grave (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) o muy grave (21)(22)(23)(24)(25)(26)(27)(28)(29)(30). El estudio de selección aportará información relevante sobre el estigma de la enfermedad de Hansen, atendiendo a los objetivos de la investigación.…”
Section: Materials Y Métodounclassified
“…The findings of this study showed that physical domainwhich mainly covers the assessment of pain and discomfort, dependence on medication or treatment, energy and fatigue, sleep and rest, mobility, daily activities and work capacityoften had lower scores in the QoL assessment in studies with leprosy patients (10,(15)(16)(17)(18)(19)(20)(21)(22)(23)44,(56)(57)(58)(59)(60)(61)(63)(64)(65) . However, it is highlighted that the change in people's lives, based on the symptoms and signs of the disease, the reactions and the development of disabilities, can lead to social isolation, work losses, difficulty in accepting the disease process and self-care; therefore, reaching not only the physical component, but also the emotional, social, and environmental component, as demonstrated in some studies (7,24,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)45,72) .…”
Section: Main Findingsmentioning
confidence: 84%
“…Other studies, in their turn, show that early diagnosis and treatment (2,5,25,39,47,70,(76)(77) , the multidisciplinary approach to the patient (10,12,15,33,41,59,65,73,(81)(82)86) , the fight against social stigma (15,25,40,63,82,86) , the development of actions aimed at the prevention and appropriate management of disabilities (5)(6)8,28,64,71,85) , health education for patients affected by leprosy (39,54,77) , and adequate follow-up in the post-discharge period (22,38,70) are critical to improve the QoL of these individuals. The study has its limitations because the evidence from observational research identified in the review shall be interpreted taking into account the possible biases inherent to the methodological design, which in itself weakens the analysis of results.…”
Section: Main Findingsmentioning
confidence: 99%